Progression of Thrombus in Portal Vein, Superior Mesenteric Vein, and Splenic Vein Even on Anticoagulation in a Patient with Ascending Colonic Malignancy with Liver Metastasis: Portal Vein Thrombosis versus Portal Vein Tumor Thrombosis - Sule, Ashish; Borja, Annamarie; Chin, Tay Jam (International Journal of Angiology, 2016)
Portal vein thrombosis (PVT) in a setting of liver metastasis is not easy to treat as it may be portal vein tumor thrombus (PVTT). A 77-year-old male patient was diagnosed as ascending colon carcinoma, underwent right hemicolectomy in 1991 with a recurrence in July 2009. In August 2009, he underwent computed tomography (CT) scan of the abdomen which showed evidence of superior mesenteric vein thrombosis with no liver metastasis. He was started with anticoagulation and decision was to treat long term. He was admitted with mesenteric artery ischemic symptoms in February 2012 on anticoagulation. CT scan abdomen and pelvis in February 2012 showed tumor thrombus involving the superior mesenteric vein, portal vein, and splenic vein with hepatic metastasis. His tumor marker chorioembryonic antigen was 34 µg/L. He was continued on anticoagulation. A repeat CT scan abdomen after 2 years (in January 2014) showed, increase in size of hepatic metastasis, extensive thrombus involving the superior mesenteric vein, portal vein, and splenic vein with collaterals. Mesentery was congested due to extensive superior mesenteric vein thrombus. He finally succumbed in June 2014. It is very important to differentiate PVT from PVTT as the prognosis is different. PVTT progresses despite of long-term anticoagulation with poor prognosis.
Keywords: anticoagulation; colon; ischemia; malignancy; portal vein; thrombosis; tumour thrombosis